2020
DOI: 10.1007/s13592-020-00796-9
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into Ethiopian honey bee diversity based on wing geomorphometric and mitochondrial DNA analyses

Abstract: Traditional beekeeping has been playing important socio-economic roles in Ethiopia for millennia. The country is situated in northeast Africa, where ranges of major evolutionary lineages of Apis mellifera adjoin. However, studies on the classification and distribution of subspecies and lineages of honey bees in the country are partly inconsistent, either proposing multiple subspecies and lineages or a unique A. m. simensis. This study was conducted with the aim of elucidating Ethiopian honey bees in reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…These honey bees have been described as a unique evolutionary lineage [3] and a subspecies [15] that differs from the honey bee populations in the neighboring countries. This was supported by a recent study on forewing geometric morphometrics and mitochondrial DNA analyses [16]. Geometric morphometry based on forewing venationinherited from both parental lines-can efficiently separate honey bee populations [38][39][40], whereas the mitochondrial genomic region commonly known as COI-COII varies among honey bee lineages in sequence length and the frequency of characteristic P and Q motifs, which can provide sufficient information to elucidate evolutionary history of maternal lineages [41].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…These honey bees have been described as a unique evolutionary lineage [3] and a subspecies [15] that differs from the honey bee populations in the neighboring countries. This was supported by a recent study on forewing geometric morphometrics and mitochondrial DNA analyses [16]. Geometric morphometry based on forewing venationinherited from both parental lines-can efficiently separate honey bee populations [38][39][40], whereas the mitochondrial genomic region commonly known as COI-COII varies among honey bee lineages in sequence length and the frequency of characteristic P and Q motifs, which can provide sufficient information to elucidate evolutionary history of maternal lineages [41].…”
Section: Introductionmentioning
confidence: 79%
“…Samples of 660 worker honey bees out of 66 managed colonies were collected from nine sites in Tigray regional state (north) and two sites in the Wendogenet local area (south), representing highland, midland and lowland AEZs of Ethiopia (Table S1). Details on sampling and study sites are provided in [16]. The samples were imported to the University of Hohenheim (Germany) in compliance with formalities stipulated by the Ethiopian Institute of Biodiversity (reference code of permit letter: EBE71/160076/2018) and subjected to morphometric and genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classification and geographical distribution of Ethiopian honey bees have been intensively discussed within the research community but methodological variations have been leading into contrasting results and opinions. While some recently published articles based on mitochondrial DNA analysis described the Ethiopian honey bees, with their evolutionary lineage Y, to be genetically distinct from other A. mellifera subspecies in neighbouring geographic areas (Boardman et al 2020;Franck et al 2001;Tihelka et al 2020), Hailu et al (2020) reported of maternal lineage O to be present in northern Ethiopia. Morphometric analysis investigating present subspecies was also not in agreement with each other (Amssalu et al 2004;Hailu et al 2021;Meixner et al 2011;Nuru et al 2002a;Radloff and Hepburn 1997;Ruttner 1988).…”
Section: Beekeeping In Ethiopiamentioning
confidence: 99%